1986
DOI: 10.1128/aac.29.4.713
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of clavulanic acid, amoxicillin, and ticarcillin against Chlamydia trachomatis

Abstract: In vitro, growth of Chlamydia trachomatis was not entirely eliminated by 960 ,ig of ticarcillin per ml, 64 ,ug of amoxicillin per ml, 32 ,ug of clavulanic acid per ml, a combination of ticarcillin (480 ,ig/ml) and clavulanic acid (32 ,ig/ml), and a combination of amoxicillin (32 ,ig/ml) and clavulanic acid (8 ,ig/ml). However, a -99% decrease in the number of inclusions was obtained at concentrations readily attainable in serum.Penicillins have partial activity against Chlamydia trachomatis both in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Our studies showed that this organism was highly susceptible to minocycline and doxycycline, as are human strains (4,24). Likewise, amoxicillin, clavulanic acid, and amoxicillin-clavulanic acid were inhibitory at low concentrations but, in keeping with other penicillins, failed to exert a complete bactericidal effect in cell culture, as was demonstrated by Bowie with clinical isolates (6). The susceptibility of C. trachomatis MoPn to azithromycin was similar to that of human strains (23).…”
Section: Discussionsupporting
confidence: 50%
“…Our studies showed that this organism was highly susceptible to minocycline and doxycycline, as are human strains (4,24). Likewise, amoxicillin, clavulanic acid, and amoxicillin-clavulanic acid were inhibitory at low concentrations but, in keeping with other penicillins, failed to exert a complete bactericidal effect in cell culture, as was demonstrated by Bowie with clinical isolates (6). The susceptibility of C. trachomatis MoPn to azithromycin was similar to that of human strains (23).…”
Section: Discussionsupporting
confidence: 50%
“…These aberrant inclusions have decreased infectivity. The effect of P-lactams on C. trachomatis and the MIC discrepancies has been well documented (2,6,9,10). In our study, the aberrant inclusions at 0.06 to 0.5 ,ug/ml in cultures incubated with penicillin failed to significantly infect new monolayers, but a few inclusions persisted.…”
Section: Discussionmentioning
confidence: 57%
“…Amoxicillin is not a treatment of choice for chlamydial infection. However, in vitro experiments have shown that ampicillin and amoxicillin each have a definite, but incomplete, inhibitory effect on C. trachomatis and C. pneumoniae at concentrations attainable in vivo (4,5,8,15,16). Masson et al (20) have shown some activity of amoxicillin-clavulanate in reducing isolation rates of C. pneumoniae from lungs in experimental mouse pneumonitis 1 day after cessation of treatment.…”
mentioning
confidence: 99%